2021
DOI: 10.3389/fmed.2021.679297
|View full text |Cite
|
Sign up to set email alerts
|

Slowed Saccadic Reaction Times in Seemingly Normal Parts of Glaucomatous Visual Fields

Abstract: Purpose: In eye movement perimetry, peripheral stimuli are confirmed by goal-directed eye movements toward the stimulus. The saccadic reaction time (SRT) is regarded as an index of visual field responsiveness, whereas in standard automated perimetry (SAP), the visual field sensitivity is tested. We investigated the relation between visual field sensitivity and responsiveness in corresponding locations of the visual field in healthy controls and in patients with mild, moderate and advanced glaucoma.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…65,67 Thepass et al supported this finding and proposed that saccade latency may serve as a useful marker of glaucoma progression prior to field loss. 75 There was also a longer latency from stimulus presentation to peak saccade velocity in glaucoma patients. 64 A more pronounced increase in latency (compared to controls) occurred with a decrease in luminance which was 67 Najjar et al 66 anti-saccade task (16 glaucoma patients and 16 controls) found an increase in errors during this task, which is known to recruit frontal brain regions and test attention/cognition.…”
Section: Dovepressmentioning
confidence: 97%
See 4 more Smart Citations
“…65,67 Thepass et al supported this finding and proposed that saccade latency may serve as a useful marker of glaucoma progression prior to field loss. 75 There was also a longer latency from stimulus presentation to peak saccade velocity in glaucoma patients. 64 A more pronounced increase in latency (compared to controls) occurred with a decrease in luminance which was 67 Najjar et al 66 anti-saccade task (16 glaucoma patients and 16 controls) found an increase in errors during this task, which is known to recruit frontal brain regions and test attention/cognition.…”
Section: Dovepressmentioning
confidence: 97%
“… 67 31 perimetric glaucoma aged 72.3 ± 7.9 ** 23 controls (not age-matched; aged 65.9 ± 5.6) Static peripheral saccade target* Reduced velocities, increased latencies, decreased accuracy in glaucoma, correlated to disease severity Thepass et al 2021. 75 76 POAG and PACG glaucoma eyes: mild n=32 (mean age 66.5, MD −2.5), moderate n= 15 (mean age 67.9, MD −9.6), advanced n=29 (mean age 68.3, MD −17.6) 58 control eyes (mean age 65.5) Eye movement perimetry (54-point) with 24–2 visual field Saccade latency increased (even in areas of preserved visual field) with glaucoma severity which was also correlated to stimulus intensity and eccentricity. Notes : *static Peripheral Stimulus: Participants View a Central Fixation Point, Which is Extinguished After a Randomised Time Period (Within a Range of a Few Seconds) and a Stationary Saccade Target Appears in the Periphery.…”
Section: Eye Movement In Glaucoma During Complex Tasksmentioning
confidence: 99%
See 3 more Smart Citations